Underperformed and Underreported Testing for Persistent Oropharyngeal Poliovirus Infections in Primary Immune Deficient Patients—Risk for Reemergence of Polioviruses. (15th June 2020) - Shulman, Lester M; Weil, Merav; Somech, Raz; Stauber, Tali; Indenbaum, Victoria; Rahav, Galia; Mendelson, Ella; Sofer, Danit
Abstract: Background: Individuals with primary immune deficiencies (PIDs) may excrete poliovirus for extended periods and remain a major reservoir for polio after eradication. Poliovirus can spread by fecal–oral or oral–oral transmission. In middle- and high-income countries, oral–oral transmission may be more prevalent than fecal–oral transmission of polioviruses where PIDs patients survive longer. Our aim was to determine the prevalence of prolonged or persistent oropharyngeal poliovirus infections in PIDs. Methods: We performed a literature search for reports of prolonged (excreting poliovirus for ≥6 months and ≤5 years) or persistent (excreting poliovirus for >5 years) poliovirus infections in PIDs. Results: There were 140 PID cases with prolonged or persistent poliovirus infections. All had poliovirus-positive stools. Testing of oropharyngeal mucosa was only reported for 6 cases, 4 of which were positive. Molecular analyses demonstrated independent evolution of poliovirus in the gut and oropharyngeal mucosa in 2 cases. Seven PIDs had multiple lineages of the same poliovirus serotype in stools without information about polioviruses in oropharyngeal mucosa. Conclusions: Testing for persistence of poliovirus in oropharyngeal mucosa of PID patients is rare, with virus recovered in 4 of 5 cases in whom stools were positive. Multiple lineages or serotypes in 7 additional PID cases may indicate separate foci of infection, some of which might be in oropharyngeal mucosa. We recommend screening throat swabs in addition to stools for poliovirus in PID patients. Containment protocols for reducing both oral–oral and fecal–oral transmission from PID patients must be formulated for hospitals and community settings. Abstract : Prolonged/persistent poliovirus infections of gut and oropharyngeal mucosa may occur in primary immune deficient patients (PIDs) with risk for oral-oral and fecal-oral transmission, however testing of oropharyngeal mucosa is underperformed and underreported. Containment protocols need to reduce both routes.